Method for the evaluation of insecticidal activity over time in Atta sexdens rubropilosa workers (Hymenoptera: Formicidae) - Nagamoto, Nilson S. [UNESP]; Forti, Luiz Carlos [UNESP]; Andrade, Ana Paula P. [UNESP]; Boaretto, Maria Aparecida C. [UNESP]; Wilcken, Carlos Frederico [UNESP] (My University, 2004)
The active ingredients used in the formulation of toxic baits for leaf-cutting ants (Hymenoptera: Formicidae) should possess a delayed action defined as an insecticidal activity whereby worker mortality is ≤15% at 24 hours and ≥90% at 21 days. Serious shortcomings have occurred in the search for new active ingredients, such as the initial selection of fenoxycarb, copper oxychloride and diflubenzuron, compounds considered very promising but whose inefficiency was verified only later, indicating methodological problems. In view of this situation, we developed a classification method for insecticidal activity over time using workers of the leaf-cutting ant Atta sexdens rubropilosa Forel. The insecticides used were fipronil, sulfluramid GX071HB and sulfluramid GX439, vehicled in an attractive pasty formulation prepared based on citrus pulp. The results obtained were consistent from a toxicological viewpoint and agreed with the literature in terms of the control of colonies. Sulfluramids were found to possess a delayed action at a broad range of concentrations, in agreement with the fact that these substances are highly effective in the control of all leaf-cutting ant species. The smaller range of concentrations of fipronil with delayed action is probably related to its lower efficacy for species more difficult to control such as Atta capiguara (Forti et al. 2003). We discuss the importance of relating behavioral particularities to the specific feeding habits of leaf-cutting ants, with methodological adequacy of the assessment of insecticides aimed at toxic baits.
Keywords: Acromyrmex; Atta; Attini; Fipronil; Sulfluramid; Toxic bait; Atta capiguara; Atta sexdens; Atta sexdens rubropilosa; Citrus; Formicidae; Hymenoptera